Pericardial hyperechogenicity and “comets” in patients with acute pericarditis but no pericardial effusion: a comparison study with age-matched healthy controls. - Sartorio, Daniele; Siniscalchi, Carmine; Reverberi, Claudio; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: According to the published data and guidelines the diagnosis of pericarditis is mainly clinical; if we exclude patients with pericardial effusion, no single study has been able to relate specific echocardiographic findings to acute pericarditis. We hypothesized that pericardial hyperechogenicity and a defined finding that we named “pericardial comets”, in analogy to lung comets, may be associated with acute pericarditis. Methods: We retrospectively analysed the echocardiograms of patients aged <50 y/o with a confirmed pericarditis diagnosis and compared them with 2 prospectively healthy controls groups (either < or > 50 y/o) to detect a potential association of pericardial hyperechogenicity and/or pericardial comets with acute pericarditis. Results: Comparison between the pericarditis and the control groups did not evidence significant differences regarding the prevalence of hyperechogenicity and pericardial comets when comparing patients with pericarditis and age-matched controls (younger than 50 years); the group of elderly healthy controls (>50 y/o) showed significantly lower prevalence of pericardial hyperechogenicity (p<0.001) and comets (p<0.001), compared with the other 2 groups. A significantly higher number of patients with pericarditis demonstrated ≥2 pericardial comets compared with age-matched controls (68% vs 48%, p=0.042). Conclusion: The echocardiographic prevalence of both pericardial hyperechogenicity and comets per patient is heavily influenced by age (inversely proportional), but the presence of at least 2 pericardial comets is significantly more frequent in patients with pericarditis than in healthy aged-matched controls. Nonetheless, this echocardiographic finding may have limited clinical usefulness, due to the frequent detection of ≥2 comets in healthy young subjects also.